FITT-Q scale a new service quality model in fitness center - Mulyono, Mulyono; Muntohir, Toho Cholik; Priambodo, Anung; Sugiharto, Sugiharto (Edelweiss Applied Science and Technology, 2024)
A study was conducted to test the measurement of Intern Fitness Center Service Quality involving 435 respondents to confirm the FITT-Q Scale (Fitness Industry Trust Tools-Quality Scale) model. The results of this study strengthened the FITT-Q Scale as an adequate measurement for fitness center service quality as it continued to demonstrate that service quality is a multidimensional construct. The alpha reliability coefficients and construct coefficients found in this study were relatively consistent with previous findings supporting the use of a simpler and less invasive version of fitness center service quality assessment.